PELAKSANAAN PERJANJIAN KERJASAMA DENGAN SISTEM BAGI HASIL WARUNG COBEK DAN GOPEK DI KOTA PEKANBARU - Salsabilla, Syafira; Lestari, Rika; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Cooperation is an agreement where a person first binds himself with another party according to the will of each of the parties. the agreement is valid as a law, then this is in accordance with Article 1338 of the Civil Code paragraph (1), namely all agreements made legally valid as law for those who make them. Warung Cobek and Gopek are one of the typical culinary businesses that offer a variety of food and drink menus, especially foods with spicy characteristics. In this writing the author focuses on the Cooperation Agreement between the owner of the Warung Cobek and Gopek with the owner of the capital. The purpose of writing this thesis: First, to find out the implementation of the cooperation agreement with the profit-sharing system for the Cobek and Gopek stalls in Pekanbaru City. Second, to determine the implementation of the principle of good faith in the implementation of the cooperation agreement with the profit-sharing system for the Cobek and Gopek stalls in Pekanbaru City. The author conducts research with sociological legal research methods, namely research conducted by conducting legal identification of how the effectiveness of law enforcement applies in society. This research is classified in the type of sociological research, because it directly conducts research on the location or point being examined to provide a complete and clear picture of the problem being examined. This research was conducted at Warung Cobek and Gopek and PT. Hensa Wisata Pekanbaru City, while the sample population was all parties related to the problems studied in this study, the data sources used, primary and secondary data, data collection techniques in this study by interviews, literature review, and data analysis. From the results of the study, there are three main things that can be concluded: First, the implementation of a cooperation agreement with a profit sharing system for Cobek and Gopek stalls in Pekanbaru City. Second, the implementation of the principle of good faith in the implementation of the cooperation agreement with the profit-sharing system for the Cobek and Gopek stalls in Pekanbaru City. The author's suggestion, in this study, is that the first party as the owner of the Warung Cobek and Gopek culinary business must fulfill achievements in the form of paying off debts to the second party as the owner of capital. This is done in order to achieve the main purpose of making an agreement. The agreement must be mutually beneficial to the parties. If the repayment of the debt does not go smoothly, then it does not heed an agreement because it is detrimental to one of the parties. With this good faith, it can make a problem that started off complicated become a little lighter because of the good faith or honesty, humility carried out by the first party. Good faith in paying off debts that should not have passed the time limit for the umpteenth time that has been determined after the relief or extension of time given by the second party.Keywords: Agreement – Cooperation